Improving Student Activities and Learning Outcomes Using PBL, TGT Models and Experimental Methods for Elementary School Students - Rahmi Wardianti, Tika Puspita Widya Rini (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
Quality education must start from the basic level, one of which is in the content of science. Science learning will obtain good learning outcomes if students are involved in all learning activities carried out. The reality that occurs shows different things because learning in the classroom is one-way, students are not given the opportunity to develop knowledge and understanding of science concepts, students' curiosity is low, learning is monotonous and boring because they use less varied learning models. The purpose of this study is to describe teacher activities, analyze student activities and student learning outcomes using Problem Based Learning models, Team Games Tournament and experimental methods. This study uses a type of classroom action research that was carried out 4 times with a total of 28 students in class V of SDN Kelayan Dalam 7 Banjarmasin. The results of the study prove that there is an increase in each meeting, namely teacher activities obtaining a score of 36 with the "very good" criterion, student activities obtaining the "All Students Very Active" criterion with a percentage of 100% and improving student learning outcomes individually and classically. This shows that the Problem Based Learning model, Team Games Tournament and experimental methods can improve student activities and learning outcomes.